How to modify an existing petrol 4stroke scooter into a CNG powered scooter, A critical analysis - Kapil Dev Sharma, Amit Kr. Sharma, Fahad Khan, Gaurav Mittal, Mehul Sharma, Prince Dubey, Sandeep Kumar Singh, Sumit Verma, Tushant Chaudhary (International Journal of Advanced Science and Technology, 2020)
In India, every 1 out of 3 households owns a two-wheeler, that alone leads to approximately 46 crores two-wheeler running around and that too only in India. Every two-wheeler runs on petrol fuel, creating a huge impact on the environment as the emission of CO2, CO, unburnt hydrocarbons is a major factor to the current situation of global warming as the fuel used is of low quality. On the other hand, when CNG(Compressed Natural Gas) is used as an alternative to petrol, it is tried and tested to effectively reduce the emission to a greater extent. Natural gas has many special specifications from high octane rating as fuel to greater performance with greater efficiency. With our country already equipped with CNG filling stations, it does not require any special preparations before CNG can fully replace petrol as a fuel in Two Wheeler. With some basic changes to the already present CNG kits, a two-wheeler can be fitted with it for a cleaner, eco-friendly environment. Keywords: CNG; Petrol; Pollution; Alternator; Efficiency; Engine; Emission; Eco-Friendly; Fuel; Safety.